Current Status of Vaccines for Porcine Reproductive and Respiratory Syndrome: Interferon Response, Immunological Overview, and Future Prospects - Jiuyi Li; Laura C. Miller; Yongming Sang (Vaccines, 2024)
Porcine reproductive and respiratory syndrome (PRRS) remains a formidable challenge for the global pig industry. Caused by PRRS virus (PRRSV), this disease primarily affects porcine reproductive and respiratory systems, undermining effective host interferon and other immune responses, resulting in vaccine ineffectiveness. In the absence of specific antiviral treatments for PRRSV, vaccines play a crucial role in managing the disease. The current market features a range of vaccine technologies, including live, inactivated, subunit, DNA, and vector vaccines, but only modified live virus (MLV) and killed virus (KV) vaccines are commercially available for PRRS control. Live vaccines are promoted for their enhanced protective effectiveness, although their ability to provide cross-protection is modest. On the other hand, inactivated vaccines are emphasized for their safety profile but are limited in their protective efficacy. This review updates the current knowledge on PRRS vaccines’ interactions with the host interferon system, and other immunological aspects, to assess their current status and evaluate advents in PRRSV vaccine development. It presents the strengths and weaknesses of both live attenuated and inactivated vaccines in the prevention and management of PRRS, aiming to inspire the development of innovative strategies and technologies for the next generation of PRRS vaccines.